Low‐cycle fatigue behavior of a newly developed cast aluminum alloy for automotive applications. Issue 9 (4th June 2019) - Mohammed, S.M.A.K.; Li, D.J.; Zeng, X.Q.; Chen, D.L.
Abstract: The drive for increasing fuel efficiency and decreasing anthropogenic greenhouse effect via lightweighting leads to the development of several new Al alloys. The effect of Mn and Fe addition on the microstructure of Al‐Mg‐Si alloy in as‐cast condition was investigated. The mechanical properties including strain‐controlled low‐cycle fatigue characteristics were evaluated. The microstructure of the as‐cast alloy consisted of globular primary α‐Al phase and characteristic Mg2 Si‐containing eutectic structure, along with Al8 (Fe, Mn)2 Si particles randomly distributed in the matrix. Relative to several commercial alloys including A319 cast alloy, the present alloy exhibited superior tensile properties without trade‐off in elongation and improved fatigue life due to the unique microstructure with fine grains and random textures. The as‐cast alloy possessed yield stress, ultimate tensile strength, and elongation of about 185 MPa, 304 MPa, and 6.3%, respectively. The stress‐strain hysteresis loops were symmetrical and approximately followed Masing behavior. The fatigue life of the as‐cast alloy was attained to be higher than that of several commercial cast and wrought Al alloys. Cyclic hardening occurred at higher strain amplitudes from 0.3% to 0.8%, while cyclic stabilization sustained at lower strain amplitudes of ≤0.2%. Examination of fractured surfaces revealed that fatigue crack initiated from the specimen surface/near‐surface, and crack propagation occurred mainly in the formation of fatigue striations.